UPAYA PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN SOSIALMELALUI MODEL PEMBELAJARAN LANGSUNG SISWA KELAS ISD NEGERI 001 UKUI SATU - Nurhamimah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
This research was motivated by the low social studies (IPS) learning outcomes of first-grade students at SD Negeri 001 Ukui Satu. Of the 20 students, only 10 students achieved learning mastery. This study aimed to improve IPS learning outcomes through the application of a direct learning model. The research was a classroom action research conducted in two cycles. The data focused on improving students’ IPS learning outcomes. The results showed an improvement in learning outcomes, starting from the initial average score of 65 with a mastery percentage of 50%. In the first cycle, the average learning outcome increased to 69.25 with a mastery percentage of 70%, and in the second cycle it further increased to 74.5 with a mastery percentage of 85%. Based on these results, it can be concluded that the application of the direct learning model can improve IPS learning outcomes of first-grade students at SD Negeri 001 Ukui Satu.